Fame amid the ruins : Italian film stardom in the age of neorealism - Gundle, Stephen, 1956- (Berghahn, 2020)
"Italian cinema gave rise to a number of the best-known films of the postwar years, from Rome Open City to Bicycle Thieves. Although some neorealist film-makers would have preferred to abolish stars altogether, the public adored them and producers needed their help in relaunching the national film industry. This book explores the many conflicts that arose in Italy between 1945 and 1953 over stars and stardom, offering intimate studies of the careers of both well-known and less familiar figures, shedding new light on the close relationship forged between cinema and society during a time of political transition and shifting national identities"--